Infeksi Parasit Gastrointestinal pada Kambing (Capra aegagrus hircus) di Desa Rajabasa Lama Kabupaten Lampung Timur - V R Pertiwi; N Riffiandi; A Sofiana (PETERPAN (Jurnal Peternakan Terapan), 2023)
In developing countries such as Indonesia, the health of small ruminants such as goats is not given much attention because the medical costs are very high, it causing a farmer to prefer to sell their livestock, even though at relatively low prices if there are signs of infection, one of which is due to parasitic diseases. This research was carried out in the village of Rajabasa Lama. The study was conducted using a descriptive method by collecting feces from the goat pens in that area using native methode and sugar floatation method Furthermore, the examination was carried out using a native test and fecal floating examination using a fluid sugar medium. The results of the examination of gastrointestinal tract parasites that were found included parasites from the protozoan Entamoeba sp. and Eimeria sp. and also parasites from the Trematoda family, the eggs of the worm Fasciola sp.. Eimeria sp. is a parasite that quite often infects ruminants, including goats. This study showed that goats in Rajabasa Lama Village had gastrointestinal parasite infections including Eimeria sp., Entamoeba sp., Fasciola sp. worm eggs, and Trichuris sp. eggs.